2011
DOI: 10.1177/0954405410395857
|View full text |Cite
|
Sign up to set email alerts
|

Design of experiments for non-manufacturing processes: benefits, challenges and some examples

Abstract: Design of Experiments (DoE) is a powerful technique for process optimization that has been widely deployed in almost all types of manufacturing processes and is used extensively in product and process design and development.There have not been as many efforts to apply powerful quality improvement techniques such as DoE to improve non-manufacturing processes. Factor levels often involve changing the way people work and so have to be handled carefully. It is even more important to get everyone working as a team.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The study about missing specialized appointments of high resolution and economic repercussion by Aragon sanitary consortium reported that out of the total appointments, 10% did not attend, the failure to attend being higher for women's first consultation in the morning without any difference regarding the weekday, being one of the most jeopardized services: rehabilitation (17.3%), gynecology (13%), traumatology (11%) and ophthalmology (10.3%) [16].…”
Section: Missing Appointments In Colombian Health Entitiesmentioning
confidence: 99%
“…The study about missing specialized appointments of high resolution and economic repercussion by Aragon sanitary consortium reported that out of the total appointments, 10% did not attend, the failure to attend being higher for women's first consultation in the morning without any difference regarding the weekday, being one of the most jeopardized services: rehabilitation (17.3%), gynecology (13%), traumatology (11%) and ophthalmology (10.3%) [16].…”
Section: Missing Appointments In Colombian Health Entitiesmentioning
confidence: 99%
“…It can be adjusted to the characteristics of the phenomena and variables under study, as well as to the type of information that is intended to be obtained from an experimental study. DoE is a flexible and cost-effective tool for developing and optimizing a process's efficiency and product's quality, as well as services, where the benefits and challenges of DoE usage are also identified [35][36][37].…”
Section: Design Of Experiments-an Overviewmentioning
confidence: 99%